Valores de referência para o teste de caminhada de seis minutos em adultos brasileiros - Labadessa, Ivana Gonçalves (2012)
Compare the values predicted by three equations referenced in the literature with the values obtained by our sample of healthy volunteers in the six minute walk test (6MWT), and establish a new reference equation for 6MWT for the Brazilian population. 89 volunteers were evaluated (43 women) 37.8 ± 15.9 years old by spirometry, assessment of physical activity level by the International Physical Activity Questionnaire (IPAQ) and performed two 6MWT with rest intervals of 30 minutes between tests. For comparison the greatest distance achieved during the 6MWT (WD-6MWT) to the equations provided we used the Friedman test with post hoc Dunn and the correlation of variables with the WD-6MWT Spearman's test and the predictive model was performed multiple linear regression analysis by stepwise method. European equation significantly overestimated (p <0.001) WD-6MWT, Brazilian and American underestimated showed no significant difference. The WD-6MWT correlated significantly with gender (r = 0.46), age (r =- 0.59), height (r = 0.57) and length of the lower limb (LL-C) (r = 0.59). The reference equation was developed WD-6MWT= 401.185 - (2.402 x age years) + (43.247 x gender 1 = male, female = 0) + (1.757 x height cm). Therefore, in view of the results obtained, it was possible to predict a new reference equation for Brazilian individuals, which explained 60% of the total variability in 6MWT, and will certainly contribute to improve the interpretation of the exercise capacity of patients with functional disability.